Efficacy and safety of tranexamic acid in intracranial haemorrhage: A meta-analysis. - Yu Xiong; Xiumei Guo; Xinyue Huang; Xiaodong Kang; Jianfeng Zhou; Chunhui Chen; Zhigang Pan; Linxing Wang; Roland Goldbrunner; Lampis Stavrinou; Pantelis Stavrinou; Shu Lin; et al. (PLoS ONE, 2023)
Background Although some studies have shown that tranexamic acid is beneficial to patients with intracranial haemorrhage, the efficacy and safety of tranexamic acid for intracranial haemorrhage remain controversial. Method The PubMed, EMBASE, and Cochrane Library databases were systematically searched. The review followed PRISMA guidelines. Data were analyzed using the random-effects model. Results Twenty-five randomized controlled trials were included. Tranexamic acid significantly inhibited hematoma growth in intracranial hemorrhage (ICH) and traumatic brain injury (TBI) patients. (ICH: mean difference -1.76, 95%CI -2.78 to -0.79, I2 = 0%, P < .001; TBI: MD -4.82, 95%CI -8.06 to -1.58, I2 = 0%, P = .004). For subarachnoid hemorrhage (SAH) patients, it significantly decreased the risk of hydrocephalus (OR 1.23, 95%CI 1.01 to 1.50, I2 = 0%, P = .04) and rebleeding (OR, 0.52, 95%CI 0.35 to 0.79, I2 = 56% P = .002). There was no significance in modified Rankin Scale, Glasgow Outcome Scale 3-5, mortality, deep vein thrombosis, pulmonary embolism, or ischemic stroke/transient ischemic. Conclusion Tranexamic acid can significantly reduce the risk of intracranial haemorrhage growth in patients with ICH and TBI. Tranexamic acid can reduce the incidence of complications (hydrocephalus, rebleeding) in patients with SAH, which can indirectly improve the quality of life of patients with intracranial haemorrhage.